(untitled) (RUNA, archivo para las ciencias del hombre, 2013)
Evaluadores Extranjeros Rachel Aisengart Menezes - UFJR, Rio Janeiro Adela Franzé - UCM, España José Reginaldo Gonçalvez - UFRJ, Brasil Ana María Rosas Mantecón - UAM Iztap., México Evaluadores Nacionales María Epele - FLACSO / CONICET Mariana Giordano - UNNE Carina Kaplan - UBA